HUMANISM AS A VALUE CATEGORY IN VIETNAMESE LITERARY STUDIES - Nguyen Dang, Hai (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
Using polysystem theory, the article examines the conceptions of literary researchers in Vietnam in establishing main standards in the process of literary evaluation. As a result, researchers often choose two basic and common standards: political and humanity. In particular, since the Renew (1986) until now, humanity standards have been considered by some researchers as a valuable category in the literary studies in Vietnam.